2020
DOI: 10.20473/j.djmkg.v53.i2.p107-110
|View full text |Cite
|
Sign up to set email alerts
|

The potential of ethanolic extract of Moringa oleifera leaves on HSF1 expression in oral cancer induced by benzo[a]pyrene

Abstract: Background: Oral cancer is the sixth most common malignancy that occurs in the world, with more than 330,000 deaths a year. In cancer, mutations occur in proteins, accompanied by unfolding proteins, caused by the unstable micro-environment in cells. To stabilise this condition, protein protectors called heat shock proteins (HSPs) are needed. HSPs are activated by a group of transcription factors known as heat shock factor 1 (HSF1). HSF1 is a considered target in cancer therapy. Moringa oleifera leaves are know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Three studies reported the effects of M. oleifera leaf extracts on rats' oral cancer. The leaf extract was administered intraorally by means of insulin sonde in three different concentrations (12)(13)(14). A study reported the efficiency of M. oleifera crude extract in the preservation of tooth extraction sockets among Cavia cobaya when administered by means of injection (15).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Three studies reported the effects of M. oleifera leaf extracts on rats' oral cancer. The leaf extract was administered intraorally by means of insulin sonde in three different concentrations (12)(13)(14). A study reported the efficiency of M. oleifera crude extract in the preservation of tooth extraction sockets among Cavia cobaya when administered by means of injection (15).…”
Section: Study Characteristicsmentioning
confidence: 99%